Turbulence near initial conditions - Steiros,K (Physical Review Fluids, 2022)
Recent observations indicate that the evolution of homogenous turbulence near its initial conditions is characterized by nonclassical, out-of-equilibrium scaling laws for the energy spectrum and dissipation rate. Based on these two observations, this work derives expressions for the evolution of the kinetic energy, interscale energy flux, and integral length scale, for homogenous decaying turbulence cascades near initial conditions. As expected, the predictions differ from those of the equilibrium Kolmogorov theory. Validation is provided using data from direct numerical simulations.